(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Steganography is the procedure that has been utilized for data holing up behind the cover object. During the time spent steganography different sorts of steganography has been utilized with the goal that data can be effectively transmitted stealthily way. In this paper different methodologies that have been utilized for data concealing procedure behind the pictures have been talked about. During the time spent picture steganography different methodologies that depend on least huge bits, Random pixel based, introduction based and AI based methodologies have been utilized. In this paper a concise report has been talked about these methodologies that can be utilized for data stowing away. Data honesty is the real worry in picture steganography process. this has been accomplished based on various security estimations that are encryption of the mystery data or insertion of the mystery data.